Avocado Seed Extract (Persea americana Mill.) Can Inhibit The Growth Of Streptococcus mutans Bacteria (In Vitro) - Tista, I Gusti Ngurah Bagus; Riany, Asri; Kusuma, I Ketut Bayu Ananda (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction The Streptococcus mutans bacteria is a key microorganism that plays a significant role in the etiology of dental caries. Avocado seed extract is one alternative used to inhibit the growth of Streptococcus mutans bacteria. Avocado seeds can act as antibacterial agents due to their active compound content, including flavonoids, saponins, tannins, alkaloids, and terpenoids. Materials and Methods. This research aims to determine the inhibitory power present in avocado seeds against Streptococcus mutans bacteria, using a pure experimental design known as Post-test Only Control Group Design. The study involves two concentrations, namely 75% and 100%, each with 6 repetitions. Avocado seed extraction uses 96% ethanol as a solvent through the maceration method. The inhibition zone testing is carried out using the Kirby-Bauer method. Results and Discussions The inhibition zones, as determined by the Kruskal-Wallis test, indicate a significant difference in both concentrations regarding the growth of Streptococcus mutans bacteria. Conclusions The conclusion of this research is that avocado seed extract can inhibit the growth of Streptococcus mutans bacteria, with the 100% concentration being more effective in creating an inhibition zone than the 75% concentration.